The Influence of Social Pressure and Beauty Standards on Women's Identity and Self-Esteem in the Context of Modernity - Annisa Ariftha; Hasan Sazali (Journal of Communication Studies, 2026)
This study aims to analyze how social pressure and beauty standards shaped by modernity influence women’s identity and self-esteem. The focus is on the role of social media and popular culture in constructing beauty standards among women aged 17–30 years. This research employs a qualitative approach using a descriptive method and a case study strategy. Data were collected through observation, in-depth interviews with four informants, and relevant literature review. The findings reveal that social media platforms, particularly Instagram and TikTok, act as primary agents in shaping homogeneous and visually oriented beauty standards. These standards generate social pressure that encourages women to conform to prevailing expectations. The internalization process occurs when external standards are adopted as part of self-evaluation, affecting confidence and body perception. However, women are not entirely passive, as they actively negotiate their identities through selective adaptation, personal interpretation, and resistance. The study highlights that beauty is a complex social construct closely linked to power relations, media representation, and identity formation in the digital era. This research contributes to communication, gender, and cultural studies, while also promoting awareness of embracing diverse forms of beauty.